Osteotomies for the Treatment of Adult Spinal Deformities: A Critical Analysis Review. Issue 5 (25th May 2022) - Yilgor, Caglar; Kindan, Peri; Yucekul, Altug; Zulemyan, Tais; Alanay, Ahmet
Abstract : » Spinal osteotomies are powerful deformity correction techniques that may be associated with serious complications. » The anatomical spinal osteotomy classification system proposes 6 grades of resection corresponding to different anatomic bone, disc, facet, and ligament interventions. » Surgeons should be aware of the nuances of 3-column osteotomies with regard to spinal level selection, construct composition, and posterior column reconstruction and closure techniques. » There is a global tendency toward avoiding 3-column osteotomies as much as possible because of the growing evidence regarding the effectiveness of posterior column osteotomies and halo-gravity traction.